2021
DOI: 10.1002/agj2.20598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mono‐, relay‐, and double‐crop systems on yield and profitability

Abstract: Diversification and intensification of cropping systems are of interest due to the potential for increased farm income. However, yield and profitability of multi-crop systems need to be understood, especially in northern environments where the growing season is short. The objective of this study was to evaluate yield and profitability of monocrop (MC), relay-intercrop (RI), and double-crop (DC) systems. A 3-yr field study was conducted in northwest Ohio with nine cropping systems, including winter wheat (Triti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Yield data used to calculate gross return were based on a 3‐yr field study conducted in northwest Ohio (Shrestha et al., 2021). …”
Section: Partial Return Of Production Systems Using Current Prices An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yield data used to calculate gross return were based on a 3‐yr field study conducted in northwest Ohio (Shrestha et al., 2021). …”
Section: Partial Return Of Production Systems Using Current Prices An...mentioning
confidence: 99%
“…The yield reduction associated with RI and DC soybean was likely due to late planting as soybean yield can be reduced as much as 0.5 bu ac −1 d −1 delay in soybean planting after the end of April (Hankinson et al., 2015; Rattalino Edreira et al., 2017). In northwest Ohio, MC soybean are generally planted mid to late May while RI and DC soybean are generally planted late May to early June and early July, respectively (Shrestha et al., 2021). On average, wheat ( Triticum aestivum L.) grown as a MC in northwest Ohio yielded 93 bu ac −1 while wheat grown in 15‐inch row width and intercropped with soybean yielded 72 bu ac −1 (Shrestha et al., 2021).…”
Section: Need For a Partial Return Calculatormentioning
confidence: 99%
“…Before entering into C agreements, farmers should carefully consider any potential yield outcomes to ensure proper payments from companies. Furthermore, additional management practices should be tested, such as the use of red clover ( Trifolium pratense L.) as a cover crop between winter wheat grain harvest and corn planting (Drury et al., 1999; Agomoh et al., 2020; Shrestha et al., 2021), the use of strip tillage (Vyn & Raimbault, 1992), or the removal of wheat straw residue (Opoku et al., 1997) to enable the potential benefit of the 3‐yr CSW rotation.…”
Section: Recommendationsmentioning
confidence: 99%
“…In this region, the area of CS rotation has expanded largely over the last several decades because of agricultural intensification, lower labor costs (Roesch‐McNally et al., 2018), and low prices for wheat grain relative to corn and soybean (USDA NASS, 2021). For instance, in Ohio, winter wheat production is often less profitable than soybean production (Shrestha et al., 2021). Consequently, the expansion of corn and soybean production, a reduction in the planting area of small‐grain crops, and an overall loss in crop diversity have been observed (Aguilar et al., 2015; Roesch‐McNally et al., 2018; Becot et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…First, the inclusion of wheat diversifies income and places less reliance on the volatile corn and soybean markets while also providing a secondary revenue stream from selling straw. Furthermore, as a fall‐planted crop, wheat provides the opportunity to double‐ or relay‐intercrop, meaning farmers can harvest two cash crops during a single year (Shrestha et al., 2021). Additionally, research has shown that including wheat in a crop rotation can increase the yield of the subsequent soybean crop by as much as 5% (Huo et al., 2022).…”
Section: Introductionmentioning
confidence: 99%